Clinical features and neonatal outcomes of neonatus with mother suspected COVID-19 in Malang, Indonesia: a serial-cases, single-centre - Brigitta Ida Resita Vebrianti Corebima; Eko Sulistijono; Setya Mithra Hartiastuti; Atiek Wulandari; Vanisia Hayu Firdayanti; Nisak Humairoh; Setya Trista Kusumawahyuni (Pediatric Sciences Journal, 2020)
Background: The COVID-19 pandemic has affected every facet of life, beginning with the first hours and days after birth, some have argued that the prudent course is to isolate infants from mothers with suspected or confirmed COVID-19. This serial-cases showed the neonate’s outcome with mother suspected COVID-19. Cases: Four neonates were born from mother with suspected or confirmed with COVID-19. The neonates were born with 7-9 APGAR score and within normal limit. All of the patients were discharged from the hospital after two days of isolation in the hospital with negative Nucleic Acid Test of SARS-CoV-2 results. Conclusion: The clinical characteristics of neonates and neonatal outcome appear very good, and these outcomes are achieved with intensive, active management, which might be the best practice in resuscitation, stabilization, bathing the baby before going to the isolation ward, and management the patient in the isolation ward